Marketing and social responsibility: an exploratory study of local tourism - Hamilton Pozo; Takeshy Tachizawa (Tourism & Management Studies)
This study developed a business management model to help stimulate social responsibility innovation and strengthen tourism in the city of Três Corações, Brazil. The research focused on identifying beliefs and values that work together to engender greater engagement and better social performance for companies mainly through innovation in order to strengthen regional tourism. The methodology used was grounded theory, which is a form of qualitative research that seeks to generate new theories through concepts, categories and properties. The proposed model both reflects social responsibility’s role in the analysed companies and helps to map the diverse socioeconomic sectors of these companies and the city’s tourism industry. The results provide evidence that marketing and social responsibility concerns are increasingly a strategic factor in tourism organisations.